The parasite cytokine mimic Hp‐TGM potently replicates the regulatory effects of TGF‐β on murine CD4+ T cells. Issue 8 (1st July 2021) - White, Madeleine P J; Smyth, Danielle J; Cook, Laura; Ziegler, Steven F; Levings, Megan K; Maizels, Rick M
Abstract: Transforming growth factor‐beta (TGF‐β) family proteins mediate many vital biological functions in growth, development and regulation of the immune system. TGF‐β itself controls immune homeostasis and inflammation, including conversion of naïve CD4 + T cells into Foxp3 + regulatory T cells (Tregs) in the presence of interleukin‐2 and T‐cell receptor ligands. The helminth parasite Heligmosomoides polygyrus exploits this pathway through a structurally novel TGF‐β mimic ( Hp ‐TGM), which binds to mammalian TGF‐β receptors and induces Tregs. Here, we performed detailed comparisons of Hp ‐TGM with mammalian TGF‐β. Compared with TGF‐β, Hp‐ TGM induced greater numbers of Foxp3 + Tregs (iTregs), with more intense Foxp3 expression. Both ligands upregulated Treg functional markers CD73, CD103 and programmed death‐ligand 1, but Hp‐ TGM induced significantly higher CD39 expression than did TGF‐β. Interestingly, in contrast to canonical TGF‐β signaling through Smad2/3, Hp‐ TGM stimulation was slower and more sustained. Gene expression profiles induced by TGF‐β and Hp‐ TGM were remarkably similar, and both types of iTregs suppressed T‐cell responses in vitro and experimental autoimmune encephalomyelitis‐driven inflammation in vivo . In vitro, both types of iTregs were equally stable under inflammatory conditions, but Hp ‐TGM‐induced iTregs were more stable in vivo during dextran sodium sulfate‐induced colitis, with greater retention of Foxp3 expression and lower conversion to a ROR‐γt + phenotype. Altogether, results from this study suggest that the parasite cytokine mimic, Hp‐ TGM, may deliver a qualitatively different signal to CD4 + T cells with downstream consequences for the long‐term stability of iTregs. These data highlight the potential of Hp‐ TGM as a new modulator of T‐cell responses in vitro and in vivo . Abstract : This study establishes that a helminth parasite protein fully mimics the immune‐suppressive effects of the mammalian cytokine transforming growth factor‐beta (TGF‐β). Named TGM (TGF‐β mimic), the parasite product drives Smad phosphorylation and induces suppressive regulatory T cells that are effective both in vitro and in vivo . Gene expression analysis confirms that despite the lack of structural similarity between TGF‐β and TGM, both ligands induce parallel responses in murine T cells. RA = Retinoic Acid.